A brief history of video games : from Atari to virtual reality - Stanton, Rich (Robinson, 2019)
A fascinating exploration of the vibrant history and culture of video games. From the first wood-panelled Pong machines in California to the masterpieces of engineering that now sit in countless homes all over the world, A Brief History of Video Games reveals the vibrant history and culture of interactive entertainment. Above all, this is a book about the games - how the experience of playing has developed from simple, repetitive beginnings into a cornucopia of genres and styles, at once utterly immersive and socially engaging. With full-colour illustrations throughout, it shows how technological advances have transformed the first dots and dashes of bored engineers into sophisticated, responsive worlds that are endlessly captivating. As thrilling and surprising as the games it describes, this is an indispensable read for anyone serious about the business of having fun.